MANAJEMEN STRATEGIS PENGEMBANGAN DESA WISATA TARO DI KABUPATEN GIANYAR - Artana, I Wayan Arta; Mau, Yesarela Pandu (AkMen JURNAL ILMIAH, 2025)
This study aims to analyze the development strategy of Taro Village in Gianyar Regency as a cultural and ecotourism-based tourist village. Taro Village has unique tourism potential, such as Balinese Hindu cultural attractions, the spiritual site of Pura Gunung Raung, and elephant conservation areas. However, inadequate management, low human resource capacity, weak digital promotion, and a non-transparent financial system are the main challenges. This study employs a qualitative descriptive approach through in-depth interviews, participatory observation, and documentation. A SWOT analysis is used to identify internal and external factors, which are then formulated into four strategies: S-O, W-O, S-T, and W-T. The research findings indicate that the S-O strategy can enhance tourism appeal by leveraging government policy support and digital technology. The W-O strategy emphasizes institutional training and mentoring. The S-T strategy is aimed at restoring the village's image through cultural promotion, while the W-T strategy focuses on institutional governance and transparency. This study concludes that the development of Taro Village requires participatory and collaborative strategic planning among stakeholders to make the village a sustainable flagship destination in Bali.